Linalool chemotype essential oil from Lippia alba in the anesthesia of fat snook (Centropomus parallelus): ventilatory rate, biochemical, antioxidant, and oxidative status parameters - Larissa N. Simões-Bueno; Carlos E. Copatti; Levy C. Gomes; Adalberto L. Val; Renan D. Amanajás; Braulio O. Caron; Berta M. Heinzmann; Bernardo Baldisserotto (Neotropical Ichthyology, 2024)
Abstract This study evaluated the anesthetic activity of essential oil from Lippia alba (EOLA), linalool chemotype in a euryhaline fish (fat snook Centropomus parallelus). In the first experiment, fish were exposed to 30, 80, 130, 180, 200, and 230 µL EOLA L−1. The second experiment evaluated smaller and larger fish with 180 µL EOLA L-1. In the third experiment, ventilatory rates (VR) for up to 120 min in animals during exposure to 5 and 10 µL EOLA L−1 were evaluated. In the fourth experiment, fish anesthetized with 30 and 180 µL EOLA L-1 were assessed at 0, 30, and 60 min after anesthesia recovery to evaluate biochemical and antioxidant parameters. The best mild and deep anesthesia times were obtained with 30 and 180 µL EOLA L-1, and larger fish had the highest times. The VR increased in fish exposed to EOLA. Blood glucose and whole-body cortisol levels were higher in fish anesthetized with 180 µL EOLA L-1. Fish exposed to EOLA had higher liver glutathione S-transferase and superoxide dismutase activities without affecting catalase and lipid peroxidation levels. The 180 µL EOLA L-1 is recommended for fat snook anesthesia because it increases VR, blood glucose, and whole-body cortisol levels and prevents oxidative stress.